Hubungan Motivasi Dan Prestasi Akademik Mahasiswa Keperawatan Saat Pembelajaran Daring Pada Situasi Pandemi Covid-19 - Indira Yobi; Juana Ivory Nababan; Risnariani Irmayanti Fua; Ni Gusti Ayu Eka; Kusman Sudarja (Universitas Malahayati Lampung, 2022)
ABSTRACT Online education is a method of imparting knowledge that makes use of the internet or computer network technology. Students' motivation can influence online learning, which can influence their academic achievement. Students are motivated to act to achieve their goals through motivation in their learning, where academic success is a result of their actions or work. Additionally, because of the Covid-19 pandemic, the method of instruction has shifted entirely online, which may affect students' motivation and academic achievement. This study aimed to identify the relationship between students' motivation and academic achievement in online learning during the Covid-19 pandemic at a private university. This study applied correlational quantitative research with a cross-sectional approach. The population in this study was 337 second-year nursing students at a private university. This study used simple random sampling. Data collection was carried out in January-March 2021. Data were analyzed using univariate and bivariate analyses. This study recruited 201 second-year nursing students. There was a significant relationship between students’ motivation and academic achievement (p-value = 0.025). Students’motivation was associated with academic achievement in online learning during the Covid-19 pandemic at a private university. Maintaining a high level of motivation is critical for online education, even more so given the current pandemic situation. As a result, both educators and students require an effective strategy for sustaining or increasing students’ motivation and academic achievement. Keywords: Motivation, Academic Achievement, Online Learning, Nursing, Student ABSTRAK Pendidikan online adalah metode penyampaian pengetahuan yang memanfaatkan teknologi internet atau jaringan komputer. Motivasi mahasiswa dapat memengaruhi pembelajaran online, yang dapat mempengaruhi prestasi akademik mereka. Mahasiswa termotivasi untuk bertindak dalam mencapai tujuannya melalui motivasi dalam belajarnya, dimana keberhasilan akademik merupakan hasil dari tindakannya tersebut. Selain itu, terdapat perubahan metode pembelajaran menjadi full online learning karena adanya pandemik Covid-19, sehingga kemungkinan dapat memengaruhi motivasi mahasiswa dan prestasi akademiknya.Tujuan penelitian ini adalah untuk mengetahui hubungan antara motivasi dan prestasi belajar dalam online learning pada mahasiswa tingkat dua selama pandemi Covid-19 di satu universitas swasta. Penelitian kuantitatif korelasional dengan pendekatan cross-sectional. Populasi pada penelitian ini adalah seluruh mahasiswa tingkat dua berjumlah 337 orang. Teknik pengambilan sampel pada penelitian adalah simple random sampling. Pengumpulan data dilaksanakan pada bulan Januari-Maret 202. Data dianalisis dengan teknik univariat dan bivariat. Penelitian ini merekrut 201 mahasiswa tingkat dua. Penelitian ini menunjukkan bahwa terdapat hubungan yang signifikan antara motivasi mahasiswa dengan prestasi akademiknya (p-value = 0.025). Terdapat hubungan antara motivasi belajar dan prestasi belajar dalam online learning pada mahasiswa tingkat dua selama pandemi Covid-19 di satu universitas swasta. Mempertahankan motivasi yang tinggi sangat penting untuk pembelajaran online learning, terutama pada saat situasi pandemi Covid-19 saat ini. Sehingga, perlu strategi yang baik bagi pendidik maupun pembelajar untuk mempertahankan atau meningkatkan motivasi mahasiswa dan prestasi akademiknya. Kata kunci: Motivasi, Prestasi Akademik, Online Learning, Keperawatan, Mahasiswa